The Effectiveness of Belimbing Wuluh Fruit Extract (Averrhoa bilimbi L) as A Smear Layer Cleanser - Asmah, Nur; Syam, Syamsiah; Sembiring, Ira Asnita; Selviani, Yusrini; Syalsabilah, Amirah (Dentistry Faculty, 2024)
Background: Root canal treatment is an effort to maintain the function and aesthetics of teeth. The smear layer is formed from the remains of instrumentation composed of organic and inorganic components. A smear layer in the tooth root canal will benefit the adhesion and colonization of microorganisms, block the action of disinfectant solutions, and prevent medicaments in the tooth root canal from penetrating the dentin tubules in the tooth root canal walls. Irrigation can be used for cleaning and disinfection in areas of the root canal that cannot be reached using instruments. Starfruit contains alkoloids, saponins, tannins, flavonoids, phenols, and triterpenoids. Objective: To determine the effectiveness of star fruit extract (Averrhoa bilimbi L) as a smear layer cleaning agent. Materials and Methods: This researcher used laboratory or experimental testing called Post Test Only Control Design. Samples were taken using the purposive sampling technique involving four treatments and six repetitions. The statistical test used is the Mann-Whiteney test. Results: Based on the Mann-Whiteney test, the test results obtained a p-value of 0.093 which is more significant than 0.05 (p-value 0.05). The results showed no significant difference between the 17% EDTA and 35% extract treatment groups regarding smear layer cleanliness. The 35% extract group is as good as the 17% EDTA group. Conclusion: star fruit extract (Averrhoa bilimbi L) is 35% effective in cleaning the smear layer.